2016
DOI: 10.1007/s40843-016-5104-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth enhancing effect of LBL-assembled magnetic nanoparticles on primary bone marrow cells

Abstract: Magnetic field has been considered to have positive effect on growth of bone. Because a magnetic nanoparticle can be regarded as one magnetic dipole, the macroscopic assemblies of magnetic nanoparticles may exhibit magnetic effect on local objects. This paper fabricated macroscopic film of γ-Fe2O3 nanoparticles by layer-by-layer (LBL) assembly on poly-D,L-lactic acid (PLA) scaffold, and studied the magnetic effect of the assembled γ-Fe2O3 nanoparticles film on primary bone marrow cells. The primary bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
4
21
0
Order By: Relevance
“…The assembly of γ-Fe 2 O 3 nanoparticles reduced the collective free energy of nanoparticles while augmenting the magnetic energy. This hypothesis can be partly supported by our conclusions in previous reports that assemblies of magnetic nanoparticles can mediate the magnetic effect on cells [13,25]. Here, we measured the magnetosensing protein by q-PCR, which was recently reported to be capable of responding to magnetic interaction (Fig.…”
Section: $57and/(6 Science China Materialssupporting
confidence: 83%
See 1 more Smart Citation
“…The assembly of γ-Fe 2 O 3 nanoparticles reduced the collective free energy of nanoparticles while augmenting the magnetic energy. This hypothesis can be partly supported by our conclusions in previous reports that assemblies of magnetic nanoparticles can mediate the magnetic effect on cells [13,25]. Here, we measured the magnetosensing protein by q-PCR, which was recently reported to be capable of responding to magnetic interaction (Fig.…”
Section: $57and/(6 Science China Materialssupporting
confidence: 83%
“…Recently, magnetic nanoparticles have shown an increasingly promising role in the construction of novel scaffolds that can impose local magnetic, thermal, and mechanic stimuli [12][13][14]. As such, tissue growth can be accelerated and some small molecules or cytokines can be released in a controlled way [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gene expression of an exogenous magnetoreceptor, an iron-sulfur cluster assembly protein 1 (ISCA1), was examined to confirm the results. An up-regulated expression of ISCA1 would be found if magnetism had significant effects [44]. However, there were no significant differences in its expression among CPC control, cIONP-CPC and DcIONP-CPC (p > .05, Figure S7(e)).…”
Section: Effects Of Magnetism In Enhancing Cellular Osteogenic Differmentioning
confidence: 92%
“…We have fabricated the macroscopic film of IONPs by layer‐by‐layer (LBL) assembly on PLA scaffold, and studied the effect of the assembled IONPs film on BMCs . The results showed that the LBL‐assembled film could promote the growth and osteogenic differentiation of cells, especially combined with the external magnetic field.…”
Section: Iopns‐based Composite Bone Scaffoldsmentioning
confidence: 99%